Entre terra e mar: história e política na narrativa oficial das forças armadas brasileiras – os casos do Exército e da Marinha - Mancuso, Amanda Pinheiro (Universidade Federal de São Carlos, 2007)
This research consists of an analysis of Army and Navy history development presented on the official history publications História do Exército Brasleiro and História Naval Brasileira, aiming at the comprehension on how public and private aspects of those two forces intercrossed for the construction of a historical speech compatible with both, the maintenance of their self-image and the reality of their intersection on nation history. By reproducing and sustaining a military ethos, this speech materializes one of the resources that can be used to understand important aspects of the military identity
Keywords: Ciência política; Guerra história; Organização militar (Forças armadas); Brasil.Marinha; Brasil.Exército; CIENCIAS HUMANAS